Altruism Characteristics of First Year Medical Students, Naresuan University - Pholchan, Thirdsak; Chuangchum, Paitoon (Srinagarind Medical Journal, 2021)
Background and objectives: Being medical professionals involves social commitment including working for others’ benefits rather than for themselves. In the stage where there is a growing sense that physicians’ altruism towards their patients is diminishing, a medical school is obliged to develop such characteristics among their students. This research was conducted to examine the characteristics of altruism in Naresuan University first year medical students. Method: A cross-sectional descriptive study was conducted. A questionnaire about altruistic characteristics was administered to 175 Naresuan University first year medical students. Frequency, percentages, standard deviation, ANOVA, F-test, and Dunnett T3 for multiple comparisons were used to analyzed the data. Results: There were 175 participants .The average score of altruistic characteristics of Naresuan University first year medical students was 3.20. It was found that there were statistically significant correlations between the method of admission and the average score at 0.05 level. Conclusion: Naresuan University first year medical students had altruistic characteristics at a moderate level. However, there were differences among students of different admission methods.